Resveratrol, Piceatannol, Curcumin, and Quercetin as Therapeutic Targets in Gastric Cancer—Mechanisms and Clinical Implications for Natural Products - Paulina Warias; Paulina Plewa; Agata Poniewierska-Baran (Molecules)
Gastric cancer remains a significant global health challenge, driving the need for innovative therapeutic approaches. Natural polyphenolic compounds such as resveratrol, piceatannol, curcumin, and quercetin currently show promising results in the prevention and treatment of various cancers, due to their diverse biological activities. This review presents the effects of natural compounds on important processes related to cancer, such as apoptosis, proliferation, migration, invasion, angiogenesis, and autophagy. Resveratrol, naturally found in red grapes, has been shown to induce apoptosis and inhibit the proliferation, migration, and invasion of gastric cancer cells. Piceatannol, a metabolite of resveratrol, shares similar anticancer properties, particularly in modulating autophagy. Curcumin, derived from turmeric, is known for its anti-inflammatory and antioxidant properties, and its ability to inhibit tumor growth and metastasis. Quercetin, a flavonoid found in various fruits and vegetables, induces cell cycle arrest and apoptosis while enhancing the efficacy of conventional therapies. Despite their potential, challenges such as low bioavailability limit their clinical application, necessitating further research into novel delivery systems. Collectively, these compounds represent a promising avenue for enhancing gastric cancer treatment and improving patient outcomes through their multifaceted biological effects.